Bentuk Dan Derajat Luka Perineum Ibu Nifas Di Wilayah Kabupaten Klaten - Triwik Sri Mulati (Poltekkes Kemenkes Surakarta, 2016)
Abstract: Perineum Laceration Type, Perineum Laceration Level, Post Partum Mother. The aim of this research was to know the descriptive of the type and the level of perineum laceration on post partum mother at Klaten. This research was descriptive design. The data were analyzed using descriptive statistics. The respondents were 84 post partum mothers who experienced perineum laceration but without complication. The result showed the majority of perineum laceration type was rupture (86.9 %) and the majority of perineum laceration level was 2ᵑᵈ level (69 %).